Anticancer potential of cryptotanshinone on breast cancer treatment; A narrative review - Dalil, Davood; Iranzadeh, Saeid; Kohansal, Soroush (Frontiers in Pharmacology, 2022)
Breast cancer has recently been known as the first lethal malignancy in women worldwide. Despite the existing treatments that have improved the patients' prognosis, some types of breast cancer are serious challenges to treat. Therefore, efforts are underway to provide more efficient therapy. Cryptotanshinone (CPT) is a liposoluble diterpenoid derivation of a traditional Chinese herbal medicine called Salvia miltiorrhiza Bunge. It has been considered in the past decades due to its vast therapeutic properties, including anti-tumor, anti-inflammatory, and anti-fibrosis. Recently, studies have found that CPT showed a significant anti-breast cancer effect in vivo and in vitro through different physiological and immunological mechanisms. This study summarized the latest research findings on the anti-breast cancer activity of CPT. Further, the main molecular mechanisms based on breast cancer types and combination with other drugs were reviewed to provide essential evidence for future longitudinal research and its clinical application in breast cancer treatment.